Road Safety Macro Assessment Model: Case Study for Hungary - Ágoston, György; Madleňák, Radovan (Periodica Polytechnica Transportation Engineering, 2021)
Road traffic crashes are a considerable concern in motorized countries because of their impact on society, economy. The number of accidents has decreased since 2000. This paper gives an overview of road safety on Hungary's road network and reviews the efforts that were done. Statistical prediction of road traffic crashes is described based on the findings of the scientific literature. Using the data provided by the Hungarian Central Statistical Office for the number of crashes and related factors for the period from 2002 to 2017, a new relationship is established between crashes and a number of related factors in an attempt to improve the models' prediction power and to investigate the effect of adding new predictors on the strength of the models.